FIGURATIVE LANGUAGE IN EVANESCENCE’S ALBUM ANYWHERE BUT HOME - Sumarno Sumarno; Purwarno Purwarno; M. Manugeren (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The research deals with figurative language, aimed to identify the types and interpret the ideas or messages implicitly or explicitly expressed with theoretical based proposed by Kennedy and Giola (2005) that figurative language is an expression of comparison that relies not on its literal meaning, but rather on its connotations. Figurative language is also commonly used in song lyrics and this is referred to as the object of the research, that is the song lyrics taken Evanescence’s album Anywhere but Home. This album consists of five songs:  Everybody’s Fool, Going under, Haunted, Taking over Me and Thoughtless. Qualitative content analysis as the use of replicable and valid method for making specific inferences from text to other states or properties of its source under Descriptive Qualitative Approach, pioneered by Krippendorff (2000) is applied here. The results show that Hyperbole, Repetition, Personification, Metaphor, Erotesis, Merism, referring to Kosasih’s category of figurative language are found in the song album with various meanings. (2007)